A Simplified Combustion Technique to Synthesize 0.1BLTO-0.9CZFO Nano Powders and Composite Ceramics with a High Magnetoelectric Coefficient - Pramukkul, Pensri; Saenkam, Kamonporn; Jantaratana, Pongsakorn; Pinitsoontorn, Supree; Chootin, Suphornphun; Bongkarn, Theerachai; Kornphom, Chiittakorn (CURRENT APPLIED SCIENCE AND TECHNOLOGY, 2025)
Nano powders and high-performance composite ceramics of 0.1Ba0.5La0.5TiO3-0.9Co0.8Zn0.2Fe2O4 (0.1BLTO-0.9CZFO) were successfully synthesized using a simplified combustion technique, using glycine as the fuel and a short process time with one calcination step. The effect of the firing temperature on the phase formation, microstructure, and density, and the optical, electrical, magnetic, and magnetoelectric properties of the ceramics were investigated. The synthesized powders were calcinated at temperatures between 600 and 1000oC for 2 h and the ceramics were sintered at temperatures in the range of 1200 to 1400oC for 2 h. The 0.1BLTO-0.9CZFO composite powder produced with a calcining temperature of 800oC, for 2 h, had a pure phase and nano sized particles (45 nm) and showed an energy band gap (Eg) of 4.85 eV and excellent magnetic properties (Ms =90.54 emu/g, Mr = 29.87 emu/g and Hc = 310 Oe). The 0.1BLTO-0.9CZFO composite ceramics showed a pure phase in all samples. The highest %phase of BLTO was 18.54%, and this was obtained with a sintering temperature at 1300oC that formed a well-packed microstructure and also gave the highest density (5.75 g/cm3). Excellent ferroelectric properties (Pmax = 1.59 μC/cm2, P10 = 0.21 μC/cm2, Ec = 9.40 kV/cm), magnetic properties (Ms = 87.31 emu/g, Mr = 20.42 emu/g, Hc = 182 Oe), and magnetoelectric coefficients (αME = 6.74 mV/cm Oe) were also obtained for the sample sintered at 1300oC for 2 h. The 0.1BLTO-0.9CZFO composite ceramics synthesized by the simplified combustion technique showed higher magnetic properties than those synthesized by conventionally sintered ceramics.